2018
DOI: 10.1016/j.ypmed.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of e-cigarette use and associations with smoking from 2012 to 2015 in an integrated healthcare delivery system

Abstract: It is unclear whether use of electronic nicotine delivery systems (ENDS) precedes cigarette smoking initiation, relapse, and/or quitting. Healthcare systems with electronic health records (EHRs) provide unique data to examine ENDS use and changes in smoking. We examined the incidence of ENDS use (2012-2015) based on clinician documentation and tested whether EHR documented ENDS use is associated with twelve-month changes in patient smoking status using a matched retrospective cohort design. The sample was Kais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 39 publications
3
45
0
2
Order By: Relevance
“…This research also suggests that dual users are more likely to attain biochemically confirmed abstinence from smoking at 1-year follow-up (8%) than are exclusive smokers (1.9%). This finding agrees with other evidence that dual use is often associated with a greater likelihood of successful cessation (eg, Zhu et al 15 and Young-Wolff et al 39 ). However, this finding must be viewed with caution because of the limitations of this study.…”
Section: Discussionsupporting
confidence: 92%
“…This research also suggests that dual users are more likely to attain biochemically confirmed abstinence from smoking at 1-year follow-up (8%) than are exclusive smokers (1.9%). This finding agrees with other evidence that dual use is often associated with a greater likelihood of successful cessation (eg, Zhu et al 15 and Young-Wolff et al 39 ). However, this finding must be viewed with caution because of the limitations of this study.…”
Section: Discussionsupporting
confidence: 92%
“…This is a key observation because of concerns that former smokers using e-cigarettes may be more likely to relapse. 23,24 One explanation for the difference in cigarette smoking abstinence among daily and non-daily e-cigarette users may be that these groups differ in their reasons for e-cigarette use, 25 such that cessation may be a less common reason for use among non-daily e-cigarette users. They may be aiming to reduce harm from cigarettes without committing to total abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is important for clinicians to accurately ascertain and record e-cigarette use in their patients. However, the current documentation of e-cigarette use in the electronic health records (EHR) is inconsistent [10]. The evidence suggests that many clinicians record e-cigarette information within the "tobacco use" section of the EHR, along with multiple combustible tobacco products (cigarettes, cigars, pipes, etc.…”
Section: Introductionmentioning
confidence: 99%